Answer:
x = 9
Explanation:
Solve for x:
11 - x/3 = 8
Put each term in 11 - x/3 over the common denominator 3: 11 - x/3 = 33/3 - x/3:
33/3 - x/3 = 8
33/3 - x/3 = (33 - x)/3:
(33 - x)/3 = 8
Multiply both sides of (33 - x)/3 = 8 by 3:
(3 (33 - x))/3 = 3×8
(3 (33 - x))/3 = 3/3×(33 - x) = 33 - x:
33 - x = 3×8
3×8 = 24:
33 - x = 24
Subtract 33 from both sides:
(33 - 33) - x = 24 - 33
33 - 33 = 0:
-x = 24 - 33
24 - 33 = -9:
-x = -9
Multiply both sides of -x = -9 by -1:
(-x)/(-1) = 9
(-1)/(-1) = 1:
Answer: x = 9